EFFECT OF PROBIOTIC "LACTOBACTERIN-TK2 " ON IMMUNOBIOLOGICAL STATUS OF NEWBORN CALVES IN THE THERAPEUTIC AND PROPHYLACTIC OF GASTROINTESTINAL DISEASES - Boranbayeva Togzhan,; Tulemissova Zhanar,; Ozkaya Serkan,; Khussainov Damir, (Scientific Journal of Pedagogy and Economics, 2020)
In recent decades, the loss of newborn calves occurs mainly from non-infectious diseases. It is established that in the process of growth and development, especially after birth, the animal has to experience the action of anthropogenic environmental factors that cause various kinds of adaptive reactions of the body. Currently, probiotic drugs are increasingly evaluated not only for their antimicrobial action but also for the characteristics of the impact on the body and its microbiota in the development of the need to strengthen the immune response, in the treatment and treatment of calf diarrhoea. It should be noted that in the modern world, a special place is occupied by studies of lactic acid bacteria associated with the development of biological products with probiotic function. The article presents the results of studying the therapeutic and prophylactic effect of the probiotic drug "Lactobacterin-TK2" in gastrointestinal diseases of newborn calves and its effect on the immune and biological status. According to the results of the study, it was found that daily feeding of the probiotic drug "Lactobacterin-TK2" to newborn calves from the moment of birth 2 times a day for 10 days increases the nonspecific resistance of the body and the safety of calves. Haematological and biochemical analysis of experimental groups of calves showed a faster normalisation of the level of alkaline phosphatase, glucose, urea, magnesium, iron, potassium, calcium, and phosphorus, which also indicates a complete recovery.